CHARACTER OF ABU IN "KAPAI-KAPAI" SCRIPT BY ARIFIN C. NOER WITH A REVIEW OF SOCIAL PSYCHOLOGY - Mas’ud, Muhammad Ali; ., indar Sabri (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
This study aims to analyze the character of Abu in the script of the drama "Kapai-Kapai" by Arifin C. Noer using a social psychology approach. This approach was chosen to understand how the social environment and psychological conditions affect the character of Abu who lives in material and spiritual poverty. The script "Kapai-Kapai" describes Abu’s struggle in seeking happiness in the midst of social and economic pressure. Abu is portrayed as a representation of the marginalized lower class, with hope being his main motivation to survive. Through sociological, psychological, and physiological analysis, the study found that Abu is a complex character, caught between reality and imagination in his quest to achieve happiness. The results of the study show that this manuscript not only reveals the socio-political conditions of his time, but also provides a reflection on the injustice and social pressure experienced by individuals like Abu. This research is expected to provide insight for readers and theater actors in understanding the character of Abu and his social context. Keywords: Character Analysis, Social Psychology, Kapai-Kapai, Arifin C. Noer, Drama, Poverty